Effects of extension services on technology adoption and productivity among female and male farmers: Summary of ESSP working paper 49 - Ragasa, Catherine; Berhane, Guush; Tadesse, Fanaye; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2013)
This study contributes new empirical evidence on the gender difference in access to extension services in Ethiopia and how this translates to observed differences in technology adoption and agricultural productivity. Our results suggest that female house-hold heads and plot managers are less likely to get extension services and are less likely to access quality services than their male counterparts. Receiving advice from development agents, as agricultural extension officers in Ethiopia are called, is strongly and positively related to adoption of improved seed and fertilizer for both female and male headed households. How-ever, visits by or advice from development agents do not significantly affect productivity, for both females and males. The re-sults highlight the need for closing the gender gap in the provision of extension services and in productivity.